The expression of emotional creativity of senior high school students in art appreciation text - Ramadhani, Elvira Kurnia; Hendri, Zulfi (citeus, 2025)
This research aims to explore: 1) the profile of emotional creativity expression in art appreciation texts; 2) how emotional creativity expression varies by grade levels; and 3) how emotional creativity expression differs by gender. The research belongs to the type of mixed methods research that utilizes the survey method. The research sample was 569 students of SMAN 4 Jember consisting of class XI and XII. Quantitative data were analyzed using descriptive statistics and non-parametric tests with the help of SPSS, while qualitative data were analyzed thematically. The results showed: 1) The majority of tends to be rational-analytical, simple vocabulary with potential for emotional diver-sity, language is quite clear but description lack integration, simple visualization with potential for imagination of emotional situations, simple meaning and moral message as an emotional reflection, searching for the reasons behind feelings through simple symbol investigation, integrating personal experiences secondarily or directly, and use of visual analogies in metaphors is still minimal and simple; 2) The quality of expres-sion of grade XI students tends to be interpretative-creative and grade XII tends to be rational-analytical but still carries interpretative-creative quality in terms of imagina-tive; 3) The quality of expression of male students tends to be interpretative-creative and female students stand out in both, namely interpretative-creative and rational-analytical. This study has proven the existence of the concept of emotional creativity in previous aesthetic development that were not explicitly mentioned.